Prestige de la hache et haches de prestige - Mélisande Bizoirre (Les Cahiers de l'École du Louvre)
In the eighteenth century, when the Iranian world was instable, the battle-axe (tabarzin in Persian) emerged as an artistic support; it bore complex decorations, inspired by that art of the book. First studied as such by A. S. Melikian-Chirvani in 1979, this group of decorate arms could henceforth be enriched, thanks to the appearance on the art market of in several museums of new specimens. By basing itself on examples bearing signatures, dates or dedications, this article highlights the diversity of forms, decorations and techniques, as well as the lines of artists working in several centres of production, including Lahore and Esfahan. It also examines the function of the arms, sometimes associated with mystic connotations, but most often symbols of power.